Patterns of Variation in the Seed Morphology of Iva annua var. macrocarpa, an Extinct North American Domesticate - Weiland, Andrew W.; Gremillion, Kristen J. (Ethnobiology Letters, 2018)
Using measurements from archaeological achenes of the extinct North American cultigen marshelder (Iva annua var. macrocarpa [S.F. Blake] R.C. Jackson), we quantitatively explore patterns of variation of fruit length and width across mid-continental North America. Linear regression shows that while achene length and width increase significantly over time (length: p-value<0.0001, b=-126.04, r2=0.1037, width: p-value<0.0001, b=-230.85, r2=0.0964), overall, regions tend to show more variation. A high incidence of phenotypic variation among domesticated marshelder as measured by coefficient of variation may be a result of introgression with wild stands. An ANOVA Tukey post-hoc analysis of archaeological site samples resulted in homogeneous subsets which correspond to region with some overlap, interpreted as a cline. These results and the low numbers of wild-sized achenes in archaeological marshelder samples of eastern Kentucky support human introduction of domesticated marshelder into this region. Marshelder in the archaeological record reflects the long-standing mixed economies of hunting-gathering and agriculture used by indigenous communities of eastern North America.